CEO Duality, Agency Costs, and Internal Capital Allocation Efficiency - Karasamani, Isabella; Andreou, Panayiotis; Aktas, Nihat; Philip, Dennis (My University, 2019)
This study examines the impact of CEO duality on firms’ internal capital allocation efficiency. We observe that when the CEO is also chair of the board, diversified firms make inefficient investments, as they allocate more capital to business segments with relatively low growth opportunities over segments with high growth opportunities. The adverse impact of CEO duality on investment efficiency prevails only among firms that face high agency problems, as captured by high free cash flows, staggered board structure and low board independence. Depending on the severity of the agency problem, CEO duality is associated with a decrease in industry-adjusted investment in high-growth segments of 1% to 2.1% over the following year, relative to that in low-growth segments. However, CEOs’ equity-based compensation curbs the negative effect of CEO duality on internal capital allocation efficiency. Overall, the findings of this study offer strong support for the agency theory and postulate the internal capital allocation policy as an important channel through which CEO duality lowers firm value in diversified firms.
Keywords: Corporate governance; Boards; Corporate boards